(untitled) (The Peerian Journal, 2025)
This study investigates the morphological characteristics of synchondrosis of the spine under conditions of experimental hypotheriosis. Structural changes, cellular responses, and tissue alterations are analyzed using histological and imaging techniques. The findings provide insights into the pathological processes and potential clinical implications for spinerelated disorders in hypothermic conditions